Implementation of dedicated social worker coaching for emergency medicine residents ‐ Lessons learned - Jennie A. Buchanan; Sarah Meadows; Jason Whitehead; W. Gannon Sungar; Christy Angerhofer; Abraham Nussbaum; Barbara Blok; Todd Guth; Katherine Bakes; Malorie Millner; Lavonne Salazar; Megan Stephens; et al. (Journal of the American College of Emergency Physicians Open, 2023)
Abstract Emergency medicine training is associated with high levels of stress and burnout, which were exacerbated by the COVID‐19 pandemic. The pandemic further exposed a mismatch between trainees' mental health needs and timely support services; therefore, the objective of our innovation was to create an opportunity for residents to access a social worker who could provide consistent coaching. The residency leadership team partnered with our graduate medical education (GME) office to identify a clinical social worker and professionally‐trained coach to lead sessions. The project was budgeted at an initial cost of $15,000 over 1 year. Residents participated in 49 group and 73 individual sessions. Post implementation in 2021, we compared this intervention to all other wellness initiatives. Resident response rate was 80.88% (n = 55/68) and median interquartile range (IQR) score of the initiative was 2 (1 = detrimental and 4 = beneficial) versus 3.79 (3.69–3.88) the median IQR of all wellness initiatives. A notable number, 22%, rated the program as detrimental, which could be related to summary comments regarding ability to attend sessions, lack of session structure, loss of personal/educational time, and capacity of the social worker to relate with them. Summary comments also revealed the innovation was useful, with individual sessions preferred to group sessions. Application of a social worker coaching program in an emergency medicine residency program appears to be a feasible novel intervention. Lessons learned after implementation include the importance of recruiting someone with emergency department/GME experience, orienting them to culture before implementation and framing coaching as an integrated residency resource.